Does being kind to yourself affect your relationship with food? : the relationship between self-compassion, intuitive eating and disordered eating among emerging adults in Aotearoa New Zealand : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University, Wellington, New Zealand - Owen, Carly Raquel (Massey University, 2023)
Emerging adults (18-25 years) have been identified as an at-risk group for disordered eating. Despite this, research regarding eating behaviours among this group in Aotearoa New Zealand is scant. Intuitive eating — the practice of honouring hunger and satiety cues — has been identified as an adaptive weight-neutral eating style associated with decreases in disordered eating and increases in well-being. Self-compassion — the ability to take a kind and accepting stance to oneself — has shown promise as a strategy that facilitates adaptive eating behaviours. However, the relationship between self-compassion, intuitive eating and disordered eating has yet to be examined in emerging adults in the Aotearoa New Zealand context. We predicted that self-compassion and intuitive eating would be negatively related to disordered eating attitudes and behaviours, and self-compassion would be positively related to intuitive eating. We also predicted that intuitive eating would mediate the relationship between self-compassion and disordered eating. A sample of 170 emerging adults in Aotearoa New Zealand completed self-report measures of self-compassion, intuitive eating and disordered eating online via Qualtrics. Pearson-moment correlations were run between variables of interest, and mediation hypotheses were tested using Hayes PROCESS macro in SPSS, entering self-compassion as the predictor, disordered eating as the outcome variable, and intuitive eating as the mediator. Results indicated that self-compassion was related to increases in intuitive eating and decreases in disordered eating; and intuitive eating was related to decreases in disordered eating. In addition, intuitive eating was a significant mediator in the relationship between self-compassion and disordered eating, such that increases in self-compassion reduced disordered eating partially through increases in intuitive eating. In other words, those that take on a more self-compassionate stance towards themselves may experience reductions in disordered eating due to increased engagement in intuitive eating practices. The outcomes of this study highlight self-compassion and intuitive eating as potentially useful constructs to integrate into prevention and treatment efforts for disordered eating among emerging adults in Aotearoa New Zealand.
Keywords: 520304 Health psychology